2017
DOI: 10.1016/j.jaci.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of egg introduction from 4 months of age in infants at risk for egg allergy

Abstract: Introduction of whole-egg powder into the diets of high-risk infants reduced sensitization to EW and induced egg-specific IgG levels. However, 8.5% of infants randomized to egg were not amenable to this primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
131
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 24 publications
1
131
0
3
Order By: Relevance
“…The proportion of infants with atopic dermatitis was reported in 5 studies (Bellach et al [15], Palmer et al [12], Perkin et al [10], Tan et al [14], Natsume et al [16]) and ranged from 9 to 100%, while 1 study that had no infants with atopic dermatitis (Palmer et al [13]). A family history of atopic diseases was reported in 62–100% of the participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of infants with atopic dermatitis was reported in 5 studies (Bellach et al [15], Palmer et al [12], Perkin et al [10], Tan et al [14], Natsume et al [16]) and ranged from 9 to 100%, while 1 study that had no infants with atopic dermatitis (Palmer et al [13]). A family history of atopic diseases was reported in 62–100% of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…In the third Australian RCT, healthy high-risk infants were randomized to receive either raw egg or rice powder from 4 months of age. Sensitization to egg at 12 months was 20 and 11% in infants randomized to placebo and egg, respectively (OR 0.46, 95% CI 0.22–0.95, p = 0.03) [14]. Bellach et al [15] also found no evidence that the consumption of raw egg starting at 4–6 months of age prevents egg allergy, as 2.1% in the treated group versus 0.6% in the placebo group developed egg allergy (RR 3.30, 95% CI 0.35–31.32, p = 0.35).…”
Section: Introductionmentioning
confidence: 99%
“…That study raises the question if such a low dose induces tolerance via hyposensitization or via primary prevention. The primary outcome in the study by Tan et al [4] was egg sensitization by allergy skin tests; however, they also had oral food challenge at 12 months, which was reported as a secondary outcome data that we and others [5] extracted for the meta-analysis. The first trial by Palmer et al [6] included only patients with eczema; however, all the other trials had patients with eczema as well (range 9–100%) [2].…”
mentioning
confidence: 99%
“…The first trial by Palmer et al [6] included only patients with eczema; however, all the other trials had patients with eczema as well (range 9–100%) [2]. Di Mario and Cattaneo suggested to exclude these three trials [3, 4, 6] from the analysis because of clinical heterogeneity. However, all three studies included in the forest plot by Di Mario et al [7-9] also had issues in clinical heterogeneity.…”
mentioning
confidence: 99%
“…The difference is huge and changes the entire perspective of what is meant by “early introduction” [3]. Other flaws of the meta-analysis that can explain the heterogeneity detected by the authors are the following: the trial by Tan et al [4] uses a different outcome measure (egg sensitization as assessed by a positive allergy skin test and not egg allergy using an oral food challenge) and presents significant loss at follow-up (more than 20%), leading to possible biases [5]; the first trial by Palmer et al [6] includes infants with eczema, an entirely different population of infants. Considering all the above, and removing the three trials [2, 4, 6] from the meta-analysis, the reduction in risk allergy is no longer significant (Fig.…”
mentioning
confidence: 99%